Qi-Fu-Yin ameliorates physiological frailty in male 5xFAD mice through remodeling the gut microbiota and modulating the cerebral cortex metabolism - Xiao, Yitong; Li, He; Han, Xinyuan; Liu, Yixiao; Sun, Jiayu; Sun, Chenxi; Wang, Yichen; Ye, Tianyuan; Cheng, Xiaorui (Frontiers in Aging Neuroscience, 2025)
IntroductionAlzheimer’s disease (AD) is a neurodegenerative disease that can only be managed rather than cured, bringing a substantial burden to society. Frailty and cognition are intertwined in a cycle of decline, affecting the prognosis of AD. Qi-Fu-Yin (QFY) is a classic prescription in traditional Chinese medicine for dementia. While most studies have focused on cognitive impairment, research on physiological frailty remains relatively scarce in AD, especially in 5xFAD mice. We aimed to investigate the impacts of QFY on the physiological frailty of male 5xFAD mice.MethodsMale 5xFAD mice received QFY, followed by grip strength test, rotarod test, grading score of frailty, lipofuscin staining, SA-β-gal and Aβ co-staining. The metabolite alteration and the intestinal flora composition were analyzed by non-targeted metabolomics and 16S rRNA sequencing. Moreover, Spearman’s correlation analysis was used to integrate behavioral results, differentially expressed metabolites, and altered bacterial genera.ResultsWe discovered that QFY improved grip strength, riding time, score of frailty, lipofuscin deposition, SA-β-gal, and Aβ in male 5xFAD mice. The results of untargeted metabolomics showed that metabolites such as proline, PS (18:1/18:0), and PFSA-CI were downregulated in the male 5xFAD mice compared with C57BJ/6JXSJL mice, while PE (18:1/18:1) was upregulated. QFY treatment reversed these changes, restoring metabolite levels toward those of C57BJ/6JXSJL mice. Arginine and proline metabolism, alanine, aspartate and glutamate metabolism, and butyrate metabolism were filtered out as the important metabolic pathways between the C57BJ/6JXSJL mice and the male 5xFAD mice, as well as between the 5xFAD mice and the 5xFAD mice with QFY treatment. Moreover, Ruminococcaceae, Subdoligranulum, Bacteroides, Alistipes, Rikenellaceae_RC9_gut_group, and Odoribacter, which were lower in male 5xFAD mice, were improved after QFY intervention.DiscussionThe differential intestinal flora might improve the metabolism of brain tissue as well as muscle strength and coordination through Short-chain fatty acids (SCFAs). The differential metabolites caused by QFY intervention also have an improving effect on physiological frailty. We suggest that QFY exerts protective impacts against the physiological frailty in AD by adjusting the muscle-gut-brain axis.